Cyclic Utilization of Zinc Borate Mother Solution via a New Method. Issue 4 (8th February 2018) - Liu, Xin; Dong, Yaping; Nai, Xueying; Wei, Ming; Li, Wu
Abstract: Zinc borate mother solution is cycled to prepare 2ZnO·3B2 O3 ·7H2 O, 3ZnO·5B2 O3 ·14H2 O, and 4ZnO·B2 O3 ·H2 O based on the properties of borate depolymerization. The results show uniform quadrilateral‐prism‐like and octahedron‐like 2ZnO·3B2 O3 ·7H2 O are synthesized at different temperatures. Flake‐like 3ZnO·5B2 O3 ·14H2 O is fabricated as reaction time prolonging, and 2ZnO·3B2 O3 ·7H2 O changed into 3ZnO·5B2 O3 ·14H2 O spontaneously. Meanwhile, resulting 2ZnO·3B2 O3 ·7H2 O is investigated to fabricate high aspect ratio of 4ZnO·B2 O3 ·H2 O whisker. Impressively, uniform 4ZnO·B2 O3 ·H2 O whisker can be resynthesized by the filtrates of 2ZnO·3B2 O3 ·7H2 O and 3ZnO·5B2 O3 ·14H2 O via the zero‐waste technology. Abstract : Zinc borate mother solution is cycled to prepare 2ZnO·3B2 O3 ·7H2 O, 3ZnO·5B2 O3 ·14H2 O, and 4ZnO·B2 O3 ·H2 O based on the properties of borate depolymerization. 2ZnO·3B2 O3 ·7H2 O is investigated to fabricate high aspect ratio of 4ZnO·B2 O3 ·H2 O whisker. Meanwhile, 4ZnO·B2 O3 ·H2 O whisker is resynthesized by the filtrates of 2ZnO·3B2 O3 ·7H2 O and 3ZnO·5B2 O3 ·14H2 O via the zero‐waste technology.